2002
DOI: 10.1080/00498250210143047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intestinal microflora on the urinary metabolic profile of rats: a 1 H-nuclear magnetic resonance spectroscopy study

Abstract: 1. Analysis of urine by (1)H-nuclear magnetic resonance (NMR) spectroscopy is used to detect biochemical disturbances predictive of toxicological changes. Recent studies, using (1)H-NMR spectroscopy have suggested that Alderley Park rats can be classified as hippuric acid (HA) or m-(hydroxyphenyl)propionic acid (m-HPPA) excretors. Evidence exists for the role of intestinal microflora in the excretion of aromatic phenolic compounds including HA and m-HPPA. 2. We sought to investigate whether intestinal microflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 16 publications
7
83
0
1
Order By: Relevance
“…Hippurate is normally found in human urine and its concentration is related to the microbial activity (49) and micro floral composition of the colon (50). The high variability in urinary hippurate concentrations in the present study is in agreement with the international literature (51,37) and may be attributable to variable intake of benzoic acid.…”
Section: Discussionsupporting
confidence: 82%
“…Hippurate is normally found in human urine and its concentration is related to the microbial activity (49) and micro floral composition of the colon (50). The high variability in urinary hippurate concentrations in the present study is in agreement with the international literature (51,37) and may be attributable to variable intake of benzoic acid.…”
Section: Discussionsupporting
confidence: 82%
“…Factors that have been shown to effect a metabolic fingerprint include strain, gender and diurnal variation, 63,64) age, 64) and intestinal microflora. 65) Some researchers have demonstrated that metabolic variation can also be due to animal cages, 66) or types of drug carrier vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have shown that multiple factors may affect metabolic characterization, including sex, strain, diurnal variations (Plumb et al, 2003;Hines et al, 2007), age (Plumb et al, 2005), intestinal microflora (Williams et al, 2002), and animal caging and handling (Robertson et al, 2002). Therefore, we made every attempt to avoid variations in the experimental procedures.…”
Section: Limitationsmentioning
confidence: 99%